A Tale of Two Gaps. Issue 2 (3rd April 2018) - Smith, Murray
Abstract: In 'Rethinking Nature, ' Shaun Gallagher makes the case for a non-reductive, naturalized phenomenology. In doing so, he seeks to close the metaphysical gap between world and mind by pursuing a 'world > mind' strategy, conforming the natural world to the world of reason and experience. Here I assess the merits of this approach by comparison with the alternative 'mind > world' strategy, whereby the the world of reason and experience is conformed to the natural world. This latter approach is exemplified by the method of 'triangulating' the mind through the integration of experiential, psychological, and neurophysiological evidence. While sympathetic to Gallagher's ambition and aspects of his approach, I raise some doubts about the anti- or non-representational model of mind that he believes his revisionist metaphysics of nature supports. Arguably, representational assumptions are built into the concepts of perception, the senses, and the mind itself. Thus, even if the metaphysical gap between mind and world can be closed, the epistemic gap between an agent and its environment must still be bridged by the engine of representation that is the extended and embodied mind.